Isolation and Diagnosis of Air Fungi inside the Buildings and Departments of the Technical Institute - Basrah Iraq - Abdulateef, Alia Mohammed (American Journal of Bioscience and Clinical Integrity, 2025)
Importance of the research: Aerobic fungi are a potential source of allergy, infection and poisoning for humans, animals and plants. Study and monitoring of aerobic fungi in indoor environments, especially those where people live or work, is essential for improving indoor air quality and preventing diseases caused by fungi. This research contributes to providing information on the diversity, distribution and impact of aerial fungi in the buildings and departments of the Technical Institute in Basra, an area characterized by a hot and humid climate. One of the goals of the research is to understand the fungal composition and the ability to spread present on the walls Surfaces and air inside buildings at the Basrah Technical Institute. The fungi were isolated from the air using the sedimentation method The method of study and from the walls using the surface swab formed the study material The types of finishing materials on wall surfaces were identified and used in the analysis. Seven types of air fungi were isolated in 6 different places at the Basra Technical Institute within the institute’s buildings and departments. Two methods were used for isolation. The first was to expose the dishes to direct air inside the buildings, and the other method was to wipe the walls of the buildings with sterile wooden sticks, then plant them on media and incubate them at a temperature 27 for filament fungi the and 37 for the growth of yeasts.After molecular diagnosis, 3 types of Candida species tropicalis clone A.A.Z.Z.N.N.6 and Candida albicans clone A.A.Z.Z.N.N.4& Candida parapsilosis clone A.A.Z.Z.N.N.5 and 2 types of Penicillium chrysogenum & Aspergillus niger were obtained.